Diopside-Ba disilicate glass-ceramic sealants for SOFCs: Enhanced adhesion and thermal stability by Sr for Ca substitution - Reddy, Allu Amarnath
This article reports on the influence of strontium for calcium substitution in diopside-Ba disilicate glass-ceramics on stabilization thermal parameters and improvement adhesion to interconnect material of SOFCs. Sr replaced 10, 20, 30 and 40% of Ca in the Ca0.9MgAl0.1La0.1Si1.9O6 component of the parent glass having the following composition, mol.%: 22.14 CaO, 24.60 MgO, 0.52 BaO, 1.23 Al2O3, 1.23 La2O3, 47.79 SiO2, 1.69 B2O3, 0.79 NiO. Si-29-MAS-NMR and Al-27 MAS-NMR spectra of the glasses revealed irrelevant chemical shifts for silicon and aluminum atoms upon changing the SrO content. T-g decreased and coefficient of thermal expansion (CTE) increased by Sr for Ca substitution in pyroxene glasses. Additionally SrO-containing glasses exhibited a viscosity of similar to 10(6) dPa s at 900 degrees C, which is suitable for joining of SOFC metallic/ceramic components by glass/glass-ceramic sealing upon stack hermetization. Glass-ceramics revealed long term (up to 1000 h) thermal stability at 900 degrees C and suitable CTE values (10.0-11.3) x 10(-6) K-1, high electrical resistivity, good adhesion and minimal reactivity with SOFC components. Copyright (c) 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.